2000
DOI: 10.1046/j.1365-2265.2000.00986.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired β‐cell function in the presence of reduced insulin sensitivity determines glucose tolerance status in acromegalic patients

Abstract: We conclude that insulin sensitivity is reduced to a similar extent in acromegalic patients with normal glucose tolerance and those with impaired glucose tolerance or diabetes. Compensatory hyperfunction of beta-cells appears to counterbalance the reduced insulin sensitivity in the acromegalic patients with normal glucose tolerance but not in those with impaired glucose tolerance or diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
105
10
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(142 citation statements)
references
References 23 publications
19
105
10
8
Order By: Relevance
“…Normalization of glucose tolerance in the present study was accompanied by an impressive improvement in insulin sensitivity, as shown by significant changes in both HOMA ISI and OGTT ISI . This is in agreement with the findings of studies based on the euglycaemic clamp (26,27) and with recent data on short-term postoperative HOMA ISI (30). Taken together, these results suggest that insulin sensitivity can improve quite quickly after surgery, whereas normalization of glucose tolerance in patients with acromegaly requires a sustained improvement of GH/IGF-I hypersecretion and insulin sensitivity.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Normalization of glucose tolerance in the present study was accompanied by an impressive improvement in insulin sensitivity, as shown by significant changes in both HOMA ISI and OGTT ISI . This is in agreement with the findings of studies based on the euglycaemic clamp (26,27) and with recent data on short-term postoperative HOMA ISI (30). Taken together, these results suggest that insulin sensitivity can improve quite quickly after surgery, whereas normalization of glucose tolerance in patients with acromegaly requires a sustained improvement of GH/IGF-I hypersecretion and insulin sensitivity.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, preoperative insulin sensitivity was impaired compared with that in controls regardless of BMI, and no significant difference in insulin sensitivity could be found between patients with NGT and IGT, supporting the view that insulin resistance is a common event in patients with acromegaly and that only those who fail to counterbalance the reduced insulin sensitivity with increased b-cell function develop IGT and diabetes mellitus (30). Interestingly, the marked postoperative improvement in insulin sensitivity observed in cured patients occurred without significant changes in BMI.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…However, treatment with pasireotide had minimal effects on hepatic or peripheral insulin sensitivity. In addition to drug-related effects, prolonged exposure to excess GH and IGF-1 in patients with acromegaly is associated with decreased insulin sensitivity (8).…”
Section: Discussionmentioning
confidence: 99%